Static Survey as Geological Engineering Method Verification of DSM Column Formation - Rafał Jendruś; Arkadiusz Stawiarski; Grzegorz Pach; Piotr Pierzyna (Geosciences, 2020)
The state-of-the-art methods for verifying the correctness of ground improvement performed using the DSM (Deep Soil Mixing) technology are largely focused on the selection of adequate factors impacting the achievement of a correct compressive strength fc [MPa] of the column core, which ensures the transfer of stress from the designed structures to the subsoil. In view of the operation of each of the columns, it is equally significant to ensure that their bases are located in load-bearing soil at the entire area of the improvement, without the need to perform many costly subsoil surveys. Based on the complementary soil investigation results and parameters obtained during deep soil mixing from an automatic logger installed on the drilling machine, a method of comparing the rotary drive pressure (working pressure) PKDK [bar] and the cone resistance qc [MPa] of the CPTU static probe (Cone Penetration Test Unit with Pore Pressure Measurement) was developed along with the method to interpret the results in the context of the correctness of the ground improvement on the construction site analyzed in this paper.